Role of PGE2 in Asthma and Nonasthmatic Eosinophilic Bronchitis - Beatriz Sastre; Victoria del Pozo (Mediators of Inflammation)
Eosinophilic bronchitis is a common cause of chronic cough, which like asthma is characterized by sputum eosinophilia, but unlike asthma there is no variable airflow obstruction or airway hyperresponsiveness. Several studies suggest that prostaglandins may play an important role in orchestrating interactions between different cells in several inflammatory diseases such as asthma. PGE2 is important because of the multiplicity of its effects on immune response in respiratory diseases; however, respiratory system appears to be unique in that PGE2 has beneficial effects. We described that the difference in airway function observed in patients with eosinophilic bronchitis and asthma could be due to differences in PGE2 production. PGE2 present in induced sputum supernatant from NAEB patients decreases BSMC proliferation, probably due to simultaneous stimulation of EP2 and EP4 receptors with inhibitory activity. This protective effect of PGE2 may not only be the result of a direct action exerted on airway smooth-muscle proliferation but may also be attributable to the other anti-inflammatory actions.